Partial regeneration of uterine horns in rats through adipose-derived stem cell sheets. Issue 5 (20th June 2018) - Sun, Huijun; Lu, Jie; Li, Bo; Chen, Shuqiang; Xiao, Xifeng; Wang, Jun; Wang, Jingjing; Wang, Xiaohong
Abstract: Severe uterine damage and infection lead to intrauterine adhesions, which result in hypomenorrhea, amenorrhea and infertility. Cell sheet engineering has shown great promise in clinical applications. Adipose-derived stem cells (ADSCs) are emerging as an alternative source of stem cells for cell-based therapies. In the present study, we investigated the feasibility of applying ADSCs as seed cells to form scaffold-free cell sheet. Data showed that ADSC sheets expressed higher levels of FGF, Col I, TGFβ, and VEGF than ADSCs in suspension, while increased expression of this gene set was associated with stemness, including Nanog, Oct4, and Sox2. We then investigated the therapeutic effects of 3D ADSCs sheet on regeneration in a rat model. We found that ADSCs were mainly detected in the basal layer of the regenerating endometrium in the cell sheet group at 21 days after transplantation. Additionally, some ADSCs differentiated into stromal-like cells. Moreover, ADSC sheets transplanted into partially excised uteri promoted regeneration of the endometrium cells, muscle cells and stimulated angiogenesis, and also resulted in better pregnancy outcomes. Therefore, ADSC sheet therapy shows considerable promise as a new treatment for severe uterine damage.